Social Accountability and Our Medical Institutions - Murtaza, Badar (Pakistan Armed Forces Medical Journal, 2022)
“Health is a state of complete physical, mental and social well-being and not merely the absence of disease or infirmity (World Health Organization).”In 1986, World Health Organization (WHO) expressed its concerns over medical schools and priority health needs. Later in the 1990s, WHO revisi-ted standards for quality assessment in medical education and medical school dominion. During this era, in 1995, WHO established the precise definition and methods of determining the social accountability of the medical institutions.The terms responsibility, responsiveness and accountability are often used regarding the social commitments of medical schools. However, Pakistani doctors, are not well-versed with these terminologies and do not appreciate the basis of these social compulsions. They are commonly used synonymously, but they express different connotations. A socially responsible medical school is dedicated to what the teaching staff naturally and instinctively considers the welfare of society.In fact; it is a situation of consciousness of duties to react to the needs of the society, which is considered the source of a “good medical practitioner”